Moderate-to-vigorous physical activity during recess and physical education among mexican elementary school students (Actividad física moderada a vigorosa durante el recreo y clase de educación física en niños mexicanos de escuela primaria) - Javier Arturo Hall-López; Paulina Yesica Ochoa-Martínez; Rodrigo Zuñiga Burruel; Edgar Ismael Alarcón Meza; Raúl Alexis Macías Castro; Pedro Sáenz-López Buñuel (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2017)
Objective: To compare the moderate-to-vigorous physical activity of physical education classes taught by teachers and their students during recess. Method: In order to determine the physical activity intensity the system for observing fitness instruction time (SOFIT) was used, a descriptive cross-sectional comparative methodological design was used, 63 physical education classes were evaluated selecting randomly four students from each class (2 men and 2 women), the same procedure was followed to evaluate the same 4 students during the 30 minutes of recess. Results: The equality of variance was calculated using the Student t test for independent samples resulting a P-value=.001 α≤ less than 0.05, with a percentage time of moderate-to-vigorous physical activity in physical education classes taught by teachers of 41%±17.7 and performed by students during recess of 50%±10.3, the percentage of difference (Δ%) was of 18% between the variables. Conclusion: The intensity of physical activity during recess was higher without teacher instruction in relation to physical education classes evaluated, due is important a feedback for the teachers in strategies for involving the students in moderate to vigorous physical activity as established by the World Health Organization. Resumen. Objetivo: Comparar la actividad física moderada a vigorosa de clases de educación física impartidas por profesores y la intensidad de la actividad física de sus estudiantes durante el recreo. Método: Se utilizó como instrumento de evaluación el sistema para observar el tiempo de instrucción de actividad física (SOFIT), el diseño metodológico fue transversal descriptivo comparativo, evaluando 63 clases de educación física seleccionado al azar cuatro estudiantes de cada clase (2 hombres y 2 mujeres), el mismo procedimiento se siguió, evaluando a los mismos 4 estudiantes durante los 30 minutos del recreo. Resultados: La igualdad de la varianza se calculó mediante la prueba t Student para muestras independientes resultando una P-Valor=.001 menor a α≤ 0.05, el porcentaje de tiempo de actividad física moderada a vigorosa en las clases de educación física impartidas por profesores fue de 41%±17.7 y la realizada por los estudiantes durante el recreo resulto en 50%±10.3 y un porcentaje de diferencia (Δ%) de 18%. Conclusión: La intensidad de actividad física durante el recreo fue mayor sin instrucción docente en relación a las clases de educación física evaluadas, por lo anterior es importante retroalimentar de manera constructiva la manera de impartir la clase de los profesores mediante capacitación con estrategias didácticas para involucrar al alumno en actividad física moderada a vigorosa como lo establece la Organización Mundial de la Salud.